2021
DOI: 10.1038/s41598-021-03421-6
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of glaucoma severity using parameters from the electroretinogram

Abstract: Glaucoma is an optic neuropathy that results in the progressive loss of retinal ganglion cells (RGCs), which are known to exhibit functional changes prior to cell loss. The electroretinogram (ERG) is a method that enables an objective assessment of retinal function, and the photopic negative response (PhNR) has conventionally been used to provide a measure of RGC function. This study sought to examine if additional parameters from the ERG (amplitudes of the a-, b-, i-wave, as well the trough between the b- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…The findings of this study build upon our previous work, further reinforcing how there is substantially more information present in the photopic ERG beyond the PhNR amplitude or ratio of PhNR to b-wave alone, 21 which currently remain the primary recommended measures for assessing RGC function on the ERG. 11 However, the improved prediction of glaucoma severity at cross-section when incorporating features from time–frequency analyses does not guarantee its improved utility for the clinically important task of predicting RGC loss in glaucoma, which remains a significant challenge.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…The findings of this study build upon our previous work, further reinforcing how there is substantially more information present in the photopic ERG beyond the PhNR amplitude or ratio of PhNR to b-wave alone, 21 which currently remain the primary recommended measures for assessing RGC function on the ERG. 11 However, the improved prediction of glaucoma severity at cross-section when incorporating features from time–frequency analyses does not guarantee its improved utility for the clinically important task of predicting RGC loss in glaucoma, which remains a significant challenge.…”
Section: Discussionsupporting
confidence: 77%
“…We have previously shown that a combination of key amplitude markers of the ERG—namely, the a-wave, b-wave, i-wave, and PhNR (PhNR1 and PhNR2) amplitudes—better predicts glaucoma severity than the PhNR amplitude alone. 21 These findings underscore how a photopic ERG contains more information about RGC function than is captured by conventional PhNR measures alone.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations